2007
DOI: 10.1002/j.2161-1939.2007.tb00025.x
|View full text |Cite
|
Sign up to set email alerts
|

What Individual Counselors Can Do to Sustain Wellness

Abstract: Individual counselors must work actively to nurture their wellness. The authors review the literature to examine what maintains wellness and what counselors can do to replenish themselves when feeling stressed, distressed, or impaired. The article provides strategies to improve resiliency in the areas of physical, emotional, cognitive, and interpersonal wellness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…In alignment with research by Venart et al, (2007) andYager andTovar-Blank (2007), students capable of recognizing their own needs, combined with the understanding of the importance of addressing impairments for the viability of the therapeutic relationship, may effectively self-advocate addressing particular issues. Unlike findings by Cooke, Bewick, Barkham, Bradley, and Audin (2006), where only 5% of psychologically vulnerable university students sought counseling, 64% of online counseling students participated in individual counseling, which may be accounted for by accuracy of self-perception in online counseling students.…”
Section: Discussionmentioning
confidence: 99%
“…In alignment with research by Venart et al, (2007) andYager andTovar-Blank (2007), students capable of recognizing their own needs, combined with the understanding of the importance of addressing impairments for the viability of the therapeutic relationship, may effectively self-advocate addressing particular issues. Unlike findings by Cooke, Bewick, Barkham, Bradley, and Audin (2006), where only 5% of psychologically vulnerable university students sought counseling, 64% of online counseling students participated in individual counseling, which may be accounted for by accuracy of self-perception in online counseling students.…”
Section: Discussionmentioning
confidence: 99%
“…"Like any stress, with sufficient intensity, it can have a negative impact on the human immune system and the quality of life in general" (Figley, 2002(Figley, , p. 1437. Counselors can experience burnout and secondary trauma reactions if they fail to recognize the impact of their work on themselves (Lambie, 2006;Lawson, 2007;Lum, 2002;O'Halloran & Linton, 2000;Venart, Vassos, & Pitcher-Heft, 2007).…”
Section: Wellness For Counselors: Why and Howmentioning
confidence: 98%
“…When stress from one facet of life cause havoc in other areas, we can fall out of balance and move down the wellness continuum into the realms of distress and impairment. As new counsellors travel the path of helping, they should expect periods of rapids and white-water-after all, every counsellor fluctuates along the wellness-impairment 14 continuum day-to-day Venart et al, 2007). What is important is that new counsellors gain awareness of this process so that they can better track and understand how they are being affected by their work on personal and professional levels.…”
Section: Risk Factorsmentioning
confidence: 99%
“…There are a variety of definitions ofwellness presented in the literature. Some researchers differentiate between types of wellness including physical, emotional, and spiritual wellness (Venart, Vassos, Pitcher-Heft, 2007), whereas others view wellness more holistically. Roscoe (2009) conducted a review of the wellness literature and found that most defmitions and models share common themes: (a) wellness is holistic and is made up of factors that interact in a complex, integrated, and synergistic fashion.…”
Section: Wellnessmentioning
confidence: 99%
See 1 more Smart Citation